2017
DOI: 10.1111/tpj.13608
|View full text |Cite
|
Sign up to set email alerts
|

GBF1 differentially regulates CAT2 and PAD4 transcription to promote pathogen defense in Arabidopsis thaliana

Abstract: G-BOX BINDING FACTOR 1 (GBF1) influences light-regulated seedling development in Arabidopsis, and inhibits CATALASE 2 (CAT2) expression during senescence. CAT2 functions as a scavenger of hydrogen peroxide. The role of GBF1 in the defense response is not known. We report here that GBF1 positively influences the defense against virulent and avirulent strains of Pseudomonas syringae. The gbf1 mutants are susceptible, whereas GBF1 over-expresser transgenic plants are resistant to bacterial pathogens. GBF1 negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 80 publications
(128 reference statements)
1
36
0
Order By: Relevance
“…EDS1 and PAD4 as part of a central regulator complex contribute to the positive feedback loop of SA accumulation [28]. PR1 is one of the genes that is induced by SA and often used as the marker for SA signaling [29]. Unexpectedly, only the expression of NPR1 was affected, which indicated that transgenic expression of FgABCC9 did not activate SA signaling.…”
Section: Resultsmentioning
confidence: 99%
“…EDS1 and PAD4 as part of a central regulator complex contribute to the positive feedback loop of SA accumulation [28]. PR1 is one of the genes that is induced by SA and often used as the marker for SA signaling [29]. Unexpectedly, only the expression of NPR1 was affected, which indicated that transgenic expression of FgABCC9 did not activate SA signaling.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to NAC and WRKY TF families, other TF family members have also been reported to regulate leaf senescence and plant immunity (Table 1). GBF1, a bZIP protein, controls leaf senescence by directly regulating PAD4 [76] and binding the promoter of CAT2 to suppress its transcription, thus resulting in the decreased H 2 O 2 -scavenging activity [75]. Accordingly, the gbf1 mutant shows a decreased H 2 O 2 level and delayed senescence phenotypes [75].…”
Section: Other Tfsmentioning
confidence: 99%
“…Accordingly, the gbf1 mutant shows a decreased H 2 O 2 level and delayed senescence phenotypes [75]. The GBF1 overexpressing plants are more resistant, whereas gbf1 is susceptible, to Pst pathogens when compared to Col-0 [76]. The circadian clock pathway is known to regulate leaf senescence and plant innate immunity [77,96].…”
Section: Other Tfsmentioning
confidence: 99%
“…In Arabidopsis, CAT1 and CAT2 gene expression can be regulated by physiological signals and transcription factors, for example Abscisic acid insensitive 5 (ABI5) in seed germination and G-box binding factor 1 (GBF1) in leaf senescence and pathogen defense (Smykowski et al, 2010;Bi et al, 2017;Giri et al, 2017). In Arabidopsis, CAT1 and CAT2 gene expression can be regulated by physiological signals and transcription factors, for example Abscisic acid insensitive 5 (ABI5) in seed germination and G-box binding factor 1 (GBF1) in leaf senescence and pathogen defense (Smykowski et al, 2010;Bi et al, 2017;Giri et al, 2017).…”
Section: Ros and Rns Metabolismmentioning
confidence: 99%
“…CAT appears to be a key target for various regulatory mechanisms. In Arabidopsis, CAT1 and CAT2 gene expression can be regulated by physiological signals and transcription factors, for example Abscisic acid insensitive 5 (ABI5) in seed germination and G-box binding factor 1 (GBF1) in leaf senescence and pathogen defense (Smykowski et al, 2010;Bi et al, 2017;Giri et al, 2017). The expression of rice OsCATA, OsCATB, and OsCATC is induced by different abiotic stresses through cis-elements in their promoters (Vighi et al, 2016).…”
Section: Ros and Rns Metabolismmentioning
confidence: 99%